Health outcomes of children born to mothers with chronic kidney disease: a pilot study - Indrani Banerjee; Stephen Powis; Mark Shevlin; Jacqueline Barnes; Audrey Soo; Alastair Sutcliffe (MDPI AG, 2010)
This study aimed to study the health of children born to mothers with chronic kidney disease. Twenty-four children born to mothers with chronic kidney disease were compared with 39 matched control children born to healthy mothers without kidney disease. The well-being of each child was individually assessed in terms of physical health, neurodevelopment and psychological health. Families participating with renal disease were more likely to be from lower socio-economic backgrounds. Significantly fewer vaginal deliveries were reported for mothers with renal disease and their infants were more likely to experience neonatal morbidity. Study and control children were comparable for growth parameters and neurodevelopment as assessed by the Griffiths scales. There was no evidence of more stress amongst mothers with renal disease or of impaired bonding between mother and child when compared to controls. However, there was evidence of greater externalizing behavioral problems in the group of children born to mothers with renal disease. Engaging families in such studies is challenging. Nonetheless, families who participated appreciated being asked. The children were apparently healthy but there was evidence in this small study of significant antenatal and perinatal morbidity compared to controls. Future larger multi-center studies are required to confirm these early findings.